Interface annealing characterization of Ti/Al/Au ohmic contacts to p-type 4H-SiC*Project supported by the Key Specific Projects of Ministry of Education of China (No. 625010101), the Specific Project of the Core Devices (No. 2013ZX01001001-004), and the Science Project of State Grid (No. SGRI-WD-71-14-004). (December 2015) - Han 韩, Chao 超; Zhang 张, Yuming 玉明; Song 宋, Qingwen 庆文; Tang 汤, Xiaoyan 晓燕; Guo 郭, Hui 辉; Zhang 张, Yimen 义门; Yang 杨, Fei 霏; Niu 钮, Yingxi 应喜
Abstract: Ti/Al/Au ohmic contacts to p-type 4H-SiC in terms of a different annealing time and Ti composition are reported. At 1050 °C, proper increase in annealing time plays a critical role in the Schottky to ohmic contact conversion. With the optimized annealing time, the contact with a high Ti content yields a lower specific contact resistivity ( ρ c ) of 6.4 × 10 −5 Ω·cm 2 compared with the low-Ti contact. The annealed surface morphology and phase resultants were examined by scanning electron microscopy (SEM) and X-ray diffraction (XRD), respectively. For the better ohmic contact, element distribution and chemical states were qualitatively identified by X-ray photoelectron spectroscopy (XPS) depth analysis. In particular, the presence of C and a Si-related phase was discussed and associated with the change in the surface status of the as-grown epilayer of 4H-SiC during annealing. The results reveal that the out-diffused C and Si atoms, with an approximate atomic ratio of 1 : 1 in the contact layer, can combine to form an amorphous Si–C state. The polycrystalline graphite instead of an unreacted C cluster in the whole alloyed structure and an extra nanosize graphite flake on the outermost surface of the annealed contact were confirmed by Raman spectroscopy.